The Myth of the Integrity and Universality of Law of the Sea: Incidents at Sea by Non-Parties of UNCLOS - Ishiii, Yurika (Indonesian Journal of International Law, 2020)
Scholarship often explains the structure of the law of the sea as a contestation and coordination of the coastal states versus the international community and the user states in terms of inclusivity and exclusivity. They tend to underscore inclusivity, as the ocean is an integrated domain. This argument is also based on the embedded idea of universality. However, such an assumption should not be taken for granted and it necessary to clarify the significance and limitations of this universality. As a part of a study for this purpose, this paper focuses on cases of incidents at sea caused by non-parties of UNCLOS that were informed by specific regional tensions and histories. It will empirically study the cases of Turkey, Venezuela and Iran, where they undertake harassing or provocative actions against foreign ships and installations. It will then reflect the significance and limits of the theories of law of the sea.